P66Shc Inactivation modifies RNS production, regulates Sirt3 activity, and improves mitochondrial homeostasis, delaying the aging process in mouse brain - Pérez, Hernán (2018)
Programmed and damage aging theories have traditionally been conceived as stand-alone schools of thought. However, the p66Shc adaptor protein has demonstrated that aging-regulating genes and reactive oxygen species (ROS) are closely interconnected, since its absence modifies metabolic homeostasis by providing oxidative stress resistance and promoting longevity. p66Shc(-/-) mice are a unique opportunity to further comprehend the bidirectional relationship between redox homeostasis and the imbalance of mitochondrial biogenesis and dynamics during aging. This study shows that brain mitochondria of p66Shc(-/-) aged mice exhibit a reduced alteration of redox balance with a decrease in both ROS generation and its detoxification activity. We also demonstrate a strong link between reactive nitrogen species (RNS) and mitochondrial function, morphology, and biogenesis, where low levels of ONOO- formation present in aged p66Shc(-/-) mouse brain prevent protein nitration, delaying the loss of biological functions characteristic of the aging process. Sirt3 modulates age-associated mitochondrial biology and function via lysine deacetylation of target proteins, and we show that its regulation depends on its nitration status and is benefited by the improved NAD+/NADH ratio in aged p66Shc(-/-) brain mitochondria. Low levels of protein nitration and acetylation could cause the metabolic homeostasis maintenance observed during aging in this group, thus increasing its lifespan.